STABILITY AND DYNAMIC PERFORMANCE BOUNDS FOR NONLINEAR MULTIVARIABLE SYSTEMS - Kouvaritakis, B; Harrison, R; Latchman, H (1987)
Earlier work on sector bounded nonlinear multivariable systems has provided dynamic performance bounds on system response, via an element-by-element L// infinity treatment. However, this approach relies on a stability criterion which is potentially conservative, since it ignores both frequency dependence and phase interrelationships. We use L//2 vector norms in conjunction with nonsimilarity scaling to retrieve this information, and hence to derive an improved stability condition. By the introduction of exponential weighting, it is shown that he L//2 stability result may be used to establish absolute bounds on system performance.